A influência da idade na aquisição da fonologia do inglês por brasileiros - Lima Júnior, Ronaldo Mangueira (2012)
This study sought to investigate how the factor ―age at the beginning of acquisition‖ influences the phonological acquisition of English by Brazilian learners who acquired the foreign language exclusively in Brazilian language classrooms and who were in the last semester of their English courses when the data were collected. Research participants were 10 learners who had begun studying English before age 12, 10 between 12 and 15, 10 after 16, and 10 native speakers of American English. All participants were recorded reading a carrier sentence containing words with the vowels [], reading a paragraph, and speaking spontaneously. The vowels were analyzed acoustically in relation to their duration and spectral quality (F1 and F2), and the other two recordings were judged in terms of intelligibility and degree of foreign accent by nine judges. In addition, all learners completed a survey that assessed extralinguistic characteristics such as motivation, desire to sound like a native speaker, degree of identification with the L2 culture, search for extra exposure to the L2, etc. The data were analyzed under the assumptions of the Complex and Dynamic Systems approach to second language acquisition (e.g. LARSEN-FREEMAN, 1997; DE BOT, 2008; CAMERON, 2003; ELLIS, 1998) and of (Acoustic-)Articulatory Phonetics (BROWMAN; GOLDSTEIN, 1987, 1993; ALBANO, 2001). The results of all analyses showed a large decrease in the quality of phonological production between native speakers and early beginners. Among the learners, though, the results did not reveal a single critical period after which L2 phonology is equally difficult or impossible to acquire, but rather a gradual tendency of greater difficulty to acquire the L2 phonology accurately as ages of onset increased. A few exceptional learners, who had phonological productions close or equal to those of native speakers, were found.